PENERAPAN SAINSTIFIK DAPAT MENINGKATKAN KEAKTIFAN SERTA HASIL BELAJAR SISWA MATERI NORMA-NORMA DALAM MASYARAKAT PEMBELAJARAN PKn DI KELAS VII SMPN 2 PANDALIAN KEC. ROKAN IV KOTO KABUPATEN ROKAN HULU - ., Mulyadi (Edu Research, 2017)
Planting the concept of norms in the life of the community and is expected that students will be ready to face the test of class increase that is ready or not ready they must face. To create a teaching material so as not to be forgotten by the students, teachers should look for methods to remind all the memory in the minds of students they have received. Teachers should be able to instill the concept of knowledge to use their long-term memory for norms in the life of society, one of which is used scientific learning. This research uses action research for three rounds. Each round consists of four stages: design, implementation and observation, reflection, and revision. The result of this research is using learning approach of science subject matter to understand the concept of norms in life of society can positively influence to student learning activity of class VII of SMP Negeri 2 Pandalian and approach of this science can be used as one of alternative of learning PKN.